Joint neutrino oscillation analysis from the T2K and NOvA experiments - S. Abubakar; M. A. Acero; B. Acharya; P. Adamson; N. Anfimov; A. Antoshkin; E. Arrieta-Diaz; L. Asquith; A. Aurisano; D. Azevedo; A. Back; N. Balashov; et al. (Nature, 2025)
Abstract The landmark discovery that neutrinos have mass and can change type (or flavour) as they propagate—a process called neutrino oscillation 1–6 —has opened up a rich array of theoretical and experimental questions being actively pursued today. Neutrino oscillation remains the most powerful experimental tool for addressing many of these questions, including whether neutrinos violate charge-parity (CP) symmetry, which has possible connections to the unexplained preponderance of matter over antimatter in the Universe 7–11 . Oscillation measurements also probe the mass-squared differences between the different neutrino mass states (Δ m 2 ), whether there are two light states and a heavier one (normal ordering) or vice versa (inverted ordering), and the structure of neutrino mass and flavour mixing 12 . Here we carry out the first joint analysis of datasets from NOvA 13 and T2K 14 , the two currently operating long-baseline neutrino oscillation experiments (hundreds of kilometres of neutrino travel distance), taking advantage of our complementary experimental designs and setting new constraints on several neutrino sector parameters. This analysis provides new precision on the $$Δ {m}_{32}^{2}$$ Δ m 32 2 mass difference, finding $$2.4{3}_{-0.03}^{+0.04}× 1{0}^{-3}\,{{\rm{eV}}}^{2}$$ 2.4 3 − 0.03 + 0.04 × 1 0 − 3 eV 2 in the normal ordering and $$-2.4{8}_{-0.04}^{+0.03}× 1{0}^{-3}\,{{\rm{eV}}}^{2}$$ − 2.4 8 − 0.04 + 0.03 × 1 0 − 3 eV 2 in the inverted ordering, as well as a 3 σ interval on δ CP of [−1.38π, 0.30π] in the normal ordering and [−0.92π, −0.04π] in the inverted ordering. The data show no strong preference for either mass ordering, but notably, if inverted ordering were assumed true within the three-flavour mixing model, then our results would provide evidence of CP symmetry violation in the lepton sector.